Profitability Analysis with Activity as a Moderating Variable in Food and Beverage Sub-Sector Companies On the Indonesia Stock Exchange - Wulandari, Aprilia Bella; Takarini, Nurjanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The food and beverage industry is a strategic sector that contributes significantly to the Indonesian economy. With rapid economic growth, companies in this sector face the challenge of optimizing financial performance, particularly profitability. This study aims to analyze the impactleverage, liquidity, and activity on profitability for companies in the beverage and food sub-sector listed on the Indonesia Stock Exchange (IDX). The method used was multiple linear regression analysis using the Moderated Regression Analysis (MRA) approach to test the moderating effect of the activity ratio. These findings indicate thatleveragenegatively contributes to profitability, while liquidity contributes positively to profitability. Activities tested through TATO (Total Asset Turnover) cannot strengthen/weaken the relationship between leverage and liquidity variables on profitability. This finding indicates the importance of liquidity management andleveragein increasing company profitability, as well as the need to pay attention to the efficiency of asset use.